An untargeted metabolomics approach reveals further insights of Lycium barbarum polysaccharides in high fat diet and streptozotocin-induced diabetic rats. (February 2019) - Xia, Hui; Tang, Huali; Wang, Feng; Yang, Xian; Wang, Zhaodan; Liu, Hechun; Pan, Da; Yang, Chao; Wang, Shaokang; Sun, Guiju
Abstract: Lycium barbarum polysaccharide (LBP), as one bioactive macromolecular abstracted from goji berry, has shown an abundance of potential function. The present study aimed to evaluate the metabolic effects of LBP on the urine and liver metabolomics on a high-fat diet and streptozotocin-induced diabetic rat model. After 8 weeks of high-fat diet and streptozotocin induction of diabetes, 24 diabetic rats were randomly allocated to the diabetic control (DC) group, LBP low, moderate, and high dosage (LBP-L, LBP-M, LBP-H) groups and 6 non-diabetic rats were established as the non-diabetic control (NDC) group for 30 days' intervention. Metabolomics was performed on liver and urine. LBP positively regulated fasting blood glucose, hemoglobin-A1c, homeostasis model assessment for insulin resistance, liver glycogen and SOD levels significantly, as compared to the DC group. Liver metabolomics showed higher levels of myo-inositol and lower levels of L-malic acid, fumaric acid, D-arabitol, L-allothreonine 1, xylitol, O-phosphorylethanolamine, ribitol, 5-methoxytryptamine 2 and digitoxose 2 in the LBP-H group vs. the DC group, which indicates that LBP may regulate the citrate cycle, alanine, aspartate and glutamate metabolism, glyoxylate and dicarboxylate metabolism. Urine metabolomics showed increased levels of creatinine, D-galacturonic acid 2, 2, 3-dihydroxybutyric acid and citric acid, and decreased levels of methylmalonic acid, benzoic acid and xylitol between the LBP-H and DC groups. The present study exhibited the effects of LBP on the urine and liver metabolomics in a high-fat diet and streptozotocin-induced rat model, which not only provides a better understanding of the anti-diabetic effects of LBP but also supplies a useful database for further specific mechanism study. Graphical abstract: Unlabelled Image Highlights: The present study provided that rat liver metabolites were disturbed by combination of the high fat diet and streptozotocin (STZ) i.p. injection. LBP regulated anti-oxidation activity, serum creatinine, and liver glycogen levels in the high fat diet and STZ-induced diabetic rats. LBP played a positive role in liver and urine metabolic profile regulation with the potential mechanism of altering TCA cycle, etc.